Desempeño profesional docente en el abordaje de dificultades de aprendizaje en estudiantes de básica media de la institución educativa “Americano”, período 2024-2025 - Rodríguez Laje, Mirian Elizabeth (2025)
This research aims to strengthen the professional performance of teachers in addressing learning difficulties among students in Basic Secondary Education at the “Americano” Basic Education School, located in the canton of La Maná, Cotopaxi province. Based on a contextual and institutional characterization, a lack of differentiated pedagogical strategies and limited teacher training to address classroom diversity were identified, which directly affects students’ academic performance and overall development.